AB0805 Panlar consensus. recommendations for the management of osteoarthritis of the hand, hip and knee. short title: pan-american league of associations for rheumatology (PANLAR) osteoarthritis (OA) study group. (15th June 2017) - Quintero, MJ; Riera, H; Espinosa, R; Souto, R; Rossi, C; Molina, JF; Salas, J; Radrigan, F; Reyes, G; Urioste, L; Papasidero, S; Garcia, A; et al.
Abstract : Background: This consensus derives from a previous study of Demographic and Clinical Characteristics by the PANLAR OA study group, reporting significant differences in handling these patients and in which it was evident the need of reaching an agreement in the management of hand, hip and knee OA in Latin America (2) Objectives: The aim is to update the recommendations for the treatment of hand, hip and knee OA by agreeing on key propositions relating to the management of hand, hip and knee OA, identifying and critically appraising research evidence for the effectiveness of the treatments and by generating recommendations based on the available evidence and expert opinion. Methods: Recommendations were developed by a group of 40 specialists made up of rheumatologists and members of other medical disciplines. A systematic review of articles, meta-analyses and guidelines for the management of hand, hip and knee OA published from 2008 and January 2014 was done. The level of evidence and strength of recommendation were classified according to the Jadad scale (3).The level of agreement was established through a Delphi technique. Results: Both "strong" and "conditional" recommendations are given for management of hand, hip and knee OA and non-pharmacological, pharmacological and surgical modalities of treatment are presented according to the different levels of agreement. Conclusions: These recommendations are based on the consensus of clinical experts from a wide range of disciplines considering the available evidence, while balancing the benefits and risks of non-pharmacological, pharmacological and surgical treatment modalities. It is hoped that these recommendations will be utilized by healthcare providers involved in the management of patients with hand, hip and knee OA. References: Reginato, Anthony M. et al. Osteoarthritis in Latin America: Study of Demographic and Clinical Characteristics in 3040 Patients. JCR: Journal of Clinical Rheumatology 21.8(2015):391–397. Jadad, A.R.; Moore R.A.; Carroll D.; Jenkinson C.; Reynolds D.J.M.; Gavaghan D.J.; McQuay H.J.(1996). Assessing the quality of reports of randomized clinical trials: Is blinding necessary? Controlled Clinical Trials 17:1–12. doi: 10.1016/0197-2456(95)00134-4. PMID 8721797. Disclosure of Interest: None declared